WORD PROCESSING AND SECOND LANGUAGE WRITING: A LONGITUDINAL CASE STUDY - Li, Jiang; Cumming, Alister (International Journal of English Studies, 2001)
The purpose of this study was to determine whether word processing might change a second language (L2) leamer's writing processes and improve the quality of his essays over a relatively long period of time. We worked from the assumption that research comparing word-processing to pen and paper composing tends to show positive results when studies include lengthy terms of data collection and when appropriate instruction and training are provided. We compared the processes and products of L2 composing displayed by a 29-year-old, male Mandarin leamer of English with intermediate proficiency in English while he wrote, over 8 months, 14 compositions grouped into 7 comparable pairs of topics altemating between uses of a lap-top computer and of pen and paper. Al1 keystrokes were recorded electronically in the computer environrnent; visual records of al1 text changes were made for the pen-and paper writing. Think-aloud protocols were recorded in al1 sessions. Analyses indicate advantages for the word-processing medium over the pen-and-paper medium in terms ofi a greater frequency of revisions made at the discourse level and at the syntactical level; higher scores for content on analytic ratings of the completed compositions; and more extensive evaluation ofwritten texts in think-aloud verbal reports.